Perkembangan Bahasa pada Anak Usia Prasekolah di Paud Terpadu Omah Bocah Annaafi’ Kelurahan Mojolangu Kecamatan Lowokwaru Kota Malang - Asfian Kaimudin; Lilla Maria; Previta Zeisar Rahmawati (Jurnal Ilmiah Kesehatan Rustida, 2020)
Development is a process of change where children learn to master higher levels of various aspects. One important aspect of development is the aspect of language development. Language is a very important communication tool in human life because besides functioning as a tool to express thoughts and feelings to others as well as a tool to understand the feelings and thoughts of others. The purpose of this study is to determine the description of language development in preschool at PAUD Terpadu Omah Bocah Annaafi’ Mojolangu village districtsof Lowokwaru, Malang City. The research design with sampling technique uses total sampling, that is 30 respondents. The instrument used in this study was a questionnaire consisting of 43 question items about children's language development, namely the Early Language Milestone Scale 2. This research used univariate data analysis. The results obtained were 27 children (90%) pass and 3 children (10%) failed. It is hoped that further researchers will assess how the child's lang age development before and after stimulation is given.